PELAKSANAAN PENGASUHAN DI TAMAN ANAK SEJAHTERA - Nurfadilah Nurfadilah; Rohita Rohita; Nila Fitria (Jurnal Ilmiah Visi, 2017)
Taman Anak Sejahtera (TAS) is one of the forms of social service which aims to provide treatment, care and protection to children of three months up to eight years. The purpose of this study is to describe the implementation of nurturing principles in TAS . The study was conducted in Jakarta as from August through October 2016 applying descriptive-qualitative method, with data collection techniques such as observation, interviews, and documentation. While, the data was analyzed using qualitative data analysis techniques. This research was conducted at TAS Lentera Nusantara in South Jakarta, TAS Akur Kurnia in East Jakarta, and TAS Kesuma in Central Jakarta. The selection of the three TAS is based on the consideration given by the Ministry of Social Affairs as the Department which supervises the existence of TAS. The results from this study revealed that caregivers can not provide care services that include health and nutrition, education, and care and protection in accordance with the objectives of TAS.